ISOLATION AND CHARACTERIZATION OF MANNANOLYTIC THERMOPHILIC BACTERIA FROM PALM OIL SHELL AND THEIR MANNANASE ENZYME PRODUCTION PROPERTIES - ANTONIUS SUWANTO; SUMARDI; MAGGY T HENAWIDJAJA; T RESNAWATI P URWADARIA (SEAMEO BIOTROP, 2005)
A mannanolytic thermophilic bacterium (L-07) was isolated from palm oil shell after 2 days ofenrichment in liquid medium supplemented with 1% palm kernel meal as mannan source. Sequenceanalysis of 16S-rRNA indicated that L-07 was similar (98%) to Geobacillus stearothermophilus, aspecies of thermophilic aerobic bacteria. We found that G. stearothermophilus L-07 producedextracellular β-1,4-mannanases, but no β-manosidase and α-galactosidase activities. The growth of L-07reached its maximum (3.0 x 106 cell/ml) at 12-20 hours, while the highest β-mannanase activity (0.52U/ml) was observed in culture medium after 36 hours of cultivation at 60oC. The medium containinglocust bean gum was the best for producing extracellular β-1,4-mannanases compared with kolang kaling,konjak, and palm kernel meal. SDS-PAGE and zymogram analysis demonstrated that crude mannanasecomplex of L-07 from locust bean gum containing medium comprised three active bands with molecularweight of 85, 73 and 50 kDa. Keywords : Extracellular enzyme/mannanase/Geobacillus stearothermophilus